Several nAChRs gene variants are associated with phenotypes of heroin addiction in Chinese Han population. (23rd March 2022) - Cai, Xintong; Zhang, Jianbo; Li, Yunxiao; Deji, Cuola; Zhou, Jinting; Li, Shengbin
Graphical abstract: Highlights: Association between polymorphisms in nAChRs genes and the severity of heroin addiction in Chinese Han population. CHRNA2 as the genetic factors contribute to daily dosage in Methadone maintenance treatment. CHRNA10 genes polymorphisms influence heroin addiction development. CHRNA5/CHRNA3/CHRNB4 nicotinic receptor clusters regulate sexual function after long term heroin addiction. Brain/Periphery regulation of nAChRs genes in heroin addiction subjective responses. Abstract: Heroin addiction is a chronic and complex brain disease. Nicotinic acetylcholine receptors (nAChRs) have been shown as major control points in many of the neurological and physiological disorders involved in heroin addiction. In the present study, thirty-three SNPs across nine nAChR genes were selected and probed for their associations with heroin addiction phenotypes in 801 unrelated northwestern Chinese Han patients. We found that rs2565055 in CHRNA2 gene was associated with daily dose of methadone treatment, and rs2672215, rs2672216 and rs2741865 in CHRNA10 gene were associated with the duration of the transition from first use to dependence (DTFUD). Cox multivariable regression analysis revealed that rs3743075, rs6495309 in CHRNA3, rs2304297 in CHRNA6, and rs1948 in CHRNB4 were associated with sexual desire in patients with heroin addiction. These findings were further supported by the identification of a haplotype block spanning CHRNA5, CHRNA3, and CHRNB4 that is correlated with changes in sexual desire after long-term heroin use. Our findings highlight associations between polymorphisms in nAChRs genes and the phenotypes of heroin addiction in the Chinese Han population. We suggest several nAChRs subunits as potential novel targets for the treatment of heroin addiction.